The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1210/jc.2011-1661
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Venous Thromboembolism in Patients with Cushing's Syndrome: A Multicenter Cohort Study

Abstract: Patients with CS are at high risk of VTE, especially during active disease and after pituitary surgery. Guidelines on thromboprophylaxis are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
148
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 33 publications
9
148
1
2
Order By: Relevance
“…High prevalence of VTE has been shown in ACTH-dependent CS than -independent after surgery. However, overall incidence rates before surgery were similar between them [2]. No difference was seen between ACTH-dependent and -independent in study 1, is compatible with the previous report.…”
Section: Study 1: Elevated D-dimer Levels Were Associated With Dvt Insupporting
confidence: 91%
See 4 more Smart Citations
“…High prevalence of VTE has been shown in ACTH-dependent CS than -independent after surgery. However, overall incidence rates before surgery were similar between them [2]. No difference was seen between ACTH-dependent and -independent in study 1, is compatible with the previous report.…”
Section: Study 1: Elevated D-dimer Levels Were Associated With Dvt Insupporting
confidence: 91%
“…2b shows the D-dimer values with the highest areas under the generally used for DVT diagnosis; this technique has a sensitivity of 97-100% and a specificity of 98-99% for proximal thrombosis [24,25] but reduced accuracy for distal thrombosis (sensitivity, 70% and specificity, 60%) [12]. We found that 7 of the 19 patients with soCS exhibited DVT (37%), which was higher than a previously reported incidence [2]. The higher prevalence of DVT might be because of the indication bias from LEU.…”
Section: Study 1: Elevated D-dimer Levels Were Associated With Dvt Inmentioning
confidence: 71%
See 3 more Smart Citations